Short Peptides from Asian Scorpions: Bioactive Molecules with Promising Therapeutic Potential - Kaiyun Xin; Ruize Sun; Wanyang Xiao; Weijie Lu; Chenhui Sun; Jietao Lou; Yanyan Xu; Tianbao Chen; Di Wu; Yitian Gao (Toxins)
Scorpion venom peptides, particularly those derived from Asian species, have garnered significant attention, offering therapeutic potential in pain management, cancer, anticoagulation, and infectious diseases. This review provides a comprehensive analysis of scorpion venom peptides, focusing on their roles as voltage-gated sodium (Nav), potassium (Kv), and calcium (Cav) channel modulators. It analyzed Nav1.7 inhibition for analgesia, Kv1.3 blockade for anticancer activity, and membrane disruption for antimicrobial effects. While the low targeting specificity and high toxicity of some scorpion venom peptides pose challenges to their clinical application, recent research has made strides in overcoming these limitations. This review summarizes the latest progress in scorpion venom peptide research, discussing their mechanisms of action, therapeutic potential, and challenges in clinical translation. This work aims to provide new insights and directions for the development of novel therapeutic drugs.